Identification of severe acute respiratory syndrome coronavirus 2 breakthrough infections by anti-nucleocapsid antibody among fully vaccinated non-healthcare workers during the transition from the delta to omicron wave - Dai, Yu-Ching; Lin, Yen-Chia; Ching, Lauren L.; Tseng, Alanna C.; Qin, Yujia; Nerurkar, Vivek R.; Wang, Wei-Kung (Frontiers in Medicine, 2022)
Uncontrolled transmission of severe acute respiratory syndrome coronavirus 2 has led to the emergence of several variants of concern (VOC). As vaccine-induced neutralizing antibodies against VOC waned over time, breakthrough infections (BTIs) have been reported primarily among healthcare workers or in long-term care facilities. Most BTIs were identified by reverse transcription-polymerase chain reaction (RT-PCR) or antigen test for individuals experiencing symptoms, known as symptomatic BTIs. In this study, we detected seroconversion of anti-nucleocapsid (N) antibody to identify both symptomatic and asymptomatic BTIs in a cohort of COVID-19-naive university employees and students following two or three doses of mRNA vaccines. We reported 4 BTIs among 85 (4.7%) participants caused by the Omicron and Delta VOC during the transition from the Delta to Omicron wave of the pandemic; three were symptomatic and confirmed by RT-PCR test and one asymptomatic. A symptomatic reinfection two and half months after a BTI was found in one participant. Two of three symptomatic BTIs and the reinfection were confirmed by whole genome sequencing. All were supported by a >4-fold increase in neutralizing antibodies against the Delta or Omicron variant. Moreover, we found both symptomatic and asymptomatic BTIs can boost neutralizing antibodies against VOC with variable degrees ranging from to 2.5- to 77.4-fold increase in neutralizing antibody titers. As BTIs continue, our findings highlight the application of anti-N antibody test to ongoing studies of immunity induced by spike-based vaccine, and provide new insights into the establishment of herd immunity in the community during the post-vaccination era.